2005
DOI: 10.1111/j.0361-3666.2005.00296.x
|View full text |Cite
|
Sign up to set email alerts
|

Making humanitarian relief networks more effective: operational coordination, trust and sense making

Abstract: Effective coordination of humanitarian assistance activities remains elusive. This paper briefly addresses some of the reasons for what is widely perceived as a coordination dilemma in humanitarian affairs and argues for a new conceptualisation of the issue. Rather than continue to request that more authority be vested in a single organisation to secure coordination through top-down control, it contends that it may be timely to consider whether relief agencies involved in an emergency should be reconceived as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
134
0
6

Year Published

2006
2006
2021
2021

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 171 publications
(141 citation statements)
references
References 15 publications
1
134
0
6
Order By: Relevance
“…The third component we identify is coordination, which is a persistent challenge and polemic in the humanitarian sector (Stephenson 2005;Bisri 2016). The introduction of new actors and new technologies promise to mitigate this challenge, even as they contribute to it in novel ways.…”
Section: Coordinationmentioning
confidence: 99%
“…The third component we identify is coordination, which is a persistent challenge and polemic in the humanitarian sector (Stephenson 2005;Bisri 2016). The introduction of new actors and new technologies promise to mitigate this challenge, even as they contribute to it in novel ways.…”
Section: Coordinationmentioning
confidence: 99%
“…Some researchers indicated that most of the humanitarian supply chain are unstable, unpredictable and stiff to respond to the needs of the affected victims [4]. This is further worsened by the fact that no single individual or group controls a relief operation [8]. More lives could be saved, and great degree of suffering could be reduced by the efficiency and effectiveness of humanitarian aid delivery in response to disasters.…”
Section: Literature Reviewmentioning
confidence: 99%
“…This coordination is particularly important between large NGOs, international relief agencies, and local authorities. 11 Inclusion of a hospital administrator has been cited as a key element of response coordination. 12 Involvement of local resources: Although local resources and providers are often eliminated or displaced by the disaster itself, their contribution can be invaluable.…”
Section: Lessons Learnedmentioning
confidence: 99%